Cytotoxicity and polyol pathway inhibitory activities of chemical constituents isolated from the pericarp of Toona sinensis - Rongshen Wang; Di Liu; Xiaoxiao Liu; Fan Liu; Lulu Xuan; Ying Tang; Wanzhong Li (Taylor & Francis, 2021)
Toona sinensis is a medicinal and edible plant that belongs to the genus Toona of family Meliaceae. Phytochemical investigations carried out on this plant, seven apotirucallane-type triterpenoids (1–7), two cycloartane-type triterpenoids (8–9), four sterols (10–13), two sesquiterpenes (14–15), four phenols (16–19), and one lignin (20) were isolated from the pericarp of T. sinensis by silica gel column and preparative middle pressure liquid chromatography. Their structures were identified by interpretation of NMR and comparison with those reported in the literature. Compounds 11–12, 15–16, and 18 were isolated from the family Meliaceae, compounds 13–14 were obtained from the genus Toona, and compound 19 was obtained from T. sinensis for the first time. Additionally, the cytotoxicity and polyol pathway (PP) inhibitory activities of active constituents were evaluated in rat glomerular mesangial cells cultured under high glucose conditions, suggesting their potential application for a PP inhibitor.
Keywords: Biochemistry; Microbiology; Pharmacology; Environmental Sciences not elsewhere classified; Chemical Sciences not elsewhere classified; Biological Sciences not elsewhere classified; Infectious Diseases